Circular Configuration of Torcular Herophili Presenting as Childhood Headache: 2D Computational Fluid Dynamic Analysis with a Proposed Mechanism - Datta, Debajyoti; Sekar, Arunkumar; Patnaik, Ashis (Asian Journal of Neurosurgery, 2023)
This case report presents a rare anatomical variant of the torcular Herophili, characterized by a circular configuration and the absence of the left transverse sinus. A 12-year-old child presented with intermittent holocranial headaches, and imaging revealed the circular torcular Herophili along with mild ventricular enlargement. The straight sinus drained into the left side of the circular torcular Herophili. Following lumbar puncture and cerebrospinal fluid (CSF) drainage, the child experienced symptom improvement. During a 6-month follow-up, the patient remained asymptomatic, without further headaches or academic disruptions. Similar to a previously reported case, the circular torcular Herophili with unilateral absent transverse sinus may be associated with impaired CSF absorption due to altered blood flow through abnormal venous anatomy. We performed two-dimensional computational fluid dynamic analysis of simulated flow through a synthetic model and showed that this circular configuration is associated with venous stasis. The venous stasis in the sinus may impair CSF absorption through the arachnoid granulations causing hydrocephalus and explaining the headache. Close monitoring and follow-up are recommended for patients with this variant. Further investigation is needed to better understand the clinical implications and underlying mechanisms of such torcular Herophili variations.
Keywords: childhood headache; confluence of sinuses; neuroanatomy; torcula; venous sinus anomaly